Innovative low noise road pavement materials studied in Portugal - Freitas, Elisabete F. (2012)
This paper deals with materials not conventionally used in road layers but widely used in the building construction to reduce noise. These materials are expanded clay aggregates and cork granulates. The former is characterized by a high porosity and was therefore used in a surface course to partially absorb the noise and the latter is characterized by a resilient behavior and was used in the binder course, to cushion the vibrations originated at the top of the pavement on the vehicles movements. Their mechanical and acoustic behaviour must be proved in laboratory before construction in real scale and surface characteristics such as skid resistance must keep a high level along the time. This paper addresses particularly these issues. The first results are very encouraging. When compared to equivalent conventional mixtures, these mixtures showed improved mechanical properties in laboratory tests. Acoustic properties, such as noise absorption, and acoustic related properties, such as damping, have also indicated a superior performance.